2014
DOI: 10.1111/add.12498
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the epidemiology of unrecorded alcohol consumption and the chemical composition of unrecorded alcohol

Abstract: Very large amounts of alcohol are produced globally that go unrecorded. The primary harm from this kind of alcohol arises from the fact that it is typically much cheaper than licit alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
172
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(178 citation statements)
references
References 142 publications
(203 reference statements)
5
172
0
1
Order By: Relevance
“…[8][9][10] Since local culture can influence the attitude of the society towards alcohol consumption and subsequently the prevalence, it is critical to repeat such studies in different sociocultural settings. 11,12 Minahasa is regency in Indonesia where traditional alcohol drinks can be easily purchased even in housebased traditional kiosks (warung) with a cheap price. Minahasa has a 3-times higher prevalence of alcohol consumption than the national prevalence of Indonesia (17.4% and 4.6%, respectively) and ranks in top-two areas with the highest rate of consumption.…”
mentioning
confidence: 99%
“…[8][9][10] Since local culture can influence the attitude of the society towards alcohol consumption and subsequently the prevalence, it is critical to repeat such studies in different sociocultural settings. 11,12 Minahasa is regency in Indonesia where traditional alcohol drinks can be easily purchased even in housebased traditional kiosks (warung) with a cheap price. Minahasa has a 3-times higher prevalence of alcohol consumption than the national prevalence of Indonesia (17.4% and 4.6%, respectively) and ranks in top-two areas with the highest rate of consumption.…”
mentioning
confidence: 99%
“…Other ingredients in alcoholic beverages, especially in beverages produced informally or illegally, have been analysed as potential causes of health problems (Kanteres et al, 2009;Lachenmeier et al, 2009;Leitz et al, 2009). However, the most comprehensive recent reviews of the research found no evidence that consumption of unrecorded alcohol is markedly linked at population level to morbidity or mortality over and above the effects of ethanol (Rehm, Kanteres & Lachenmeier, 2010;Rehm et al, 2014).…”
Section: Quality Of Alcohol Consumedmentioning
confidence: 99%
“…As unrecorded products are often available outside the regulated market (resulting e.g. in cheaper prices, different controls, or no controls on availability), they may increase overall consumption and have also been linked to more heavy drinking occasions (Rehm et al, 2014). …”
Section: Quality Of Alcohol Consumedmentioning
confidence: 99%
See 2 more Smart Citations